EFFECTS OF MODIFIED TRANSCUTANEOUS ELECTROMAGNETIC FIELD IRRADIATION ON ACUTE HEART RATE VARIABILITY RESPONSES (CIPEEX, 2025)
Introduction: Photobiomodulation is a non-thermal therapy that uses light in the visible spectrum and interacts with cells and tissues, being absorbed by mitochondrial chromophores. The application of photobiomodulation for the analysis of cardiac physiological parameters, especially HRV, represents a pioneering field of study that warrants further investigation. Objective: to analyze the acute effect of ILIB (Intravascular Laser Irradiation of Blood) therapy on heart rate variability (HRV) outcomes in the time domain. Methodology: 20 participants of both sexes, aged between 18 and 60 years, were included in the sample. The study was conducted in three visits: the first to collect baseline physiological data, and the two subsequent visits randomized for the application of radial ILIB or placebo. Results: HRV was analyzed in the time domain, and the results showed a significant reduction in resting HR (p=0.0024) and an increase in RR interval variability (p=0.0047) induced by ILIB. The SDNN variable also increased after the ILIB irradiation intervention (p=0.012), however, there were no significant differences between interventions for the RMSSD variable (p=0.081). Conclusion: The results suggest promising effects of ILIB on HRV modulation. However, there are discrepancies in the results between the different HRV variables, indicating the complexity of the mechanisms involved in cardiovascular function.
Keywords: Photobiomodulation; Heart Rate Variability; ILIB; Health